Summing multilinear operators and sequence classes - Botelho, Geraldo; Freitas, Davidson (Topological Methods in Nonlinear Analysis, 2024)
We construct a general framework that generates classes of multilinear operators between Banach spaces which encompasses, as particular cases, the several classes of summing type multilinear operators that have been studied individually in the literature. Summing operators by blocks in the isotropic and anisotropic cases are taken into account. The classes we create are shown to be Banach ideals of multilinear operators and applications to coherence and coincidence theorems are provided.